MANAJEMEN USAHA PENANGKAPAN IKAN DI PELABUHAN PERIKANAN PANTAI SADENG KABUPATEN GUNUNG KIDUL - Resna Trimerani; Lestari Rahayu Waluyati; Jamhari Jamhari (Agro Ekonomi, 2014)
This research aims to discover the suitability of the rights and obligations of the owners of the land, the helmsman and the crews; finding out the value of the investment and operating costm the revenue of the owners of the land, the helmsman and the crews profit sharing system and management of fishing attempt; finding out the effect of social capital ( trust, norms, social networks)and non social capital ( education, age, experience) towards the result of fishing. The sample of respondents were the owners of motor vessels using gillnet and handline fishing gears, the helmsman and the crews.Data analysis tool used was the Likert Scale which was then processed using multiple linear regressions. This research result showed that the owners of the land are obliged to provide the means of production and the operating cost during the fishing attempt and has the right to determine their fish catch marketing chain. The helmsman takes full responsibility during the fishing attempt including supervising the crews work, and the crews are obliged to work well during fishing. The systems of revenue sharing is 50%-50%. The ratio of net income towards the cost of the land owners, the helmsman, and the crews is bigger than the interest rate. The phase of the managements of fishing attempt includes planning, organizing, implementing, monitoring, and evaluation. Social capital in the form of trust and norms as well as non-social capital in the form of education and experience give positive effects to inceas fish catch.